Long-term programme of biophysical monitoring of the personnel involved in the construction of the new safe confinement - Berkovskyy, V.; Bonchuk, Iu.; Ratia, G.; Tsygankov, M.; Vasylenko, V.; Sakhno, V.; Volkerniuk, T.; Gorbachov, S. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2017)
The international Shelter Implementation Plan (SIP) foresees a step-by-step transformation of the Chornobyl site into the safe condition. The New Safe Confinement (NSC), is an unprecedented 108-meter tall structure over the destroyed Unit 4 of the Chernobyl Nuclear Power Plant, and is a central element of SIP. Many workers involved in SIP may have a direct contact with fragments of the irradiated fuel, fuel-containing aerosols, and other contaminated material at the Chornobyl industrial site. Isotopes of plutonium, americium, strontium, and cesium are dominating in internal exposure of SIP workers. The safety of workers is a high priority of SIP. Starting from 2004 the Ukrainian Radiation Protection Institute (RPI) is performing a large-scale Internal Dosimetry Program as an integral part of SIP. Pu contents in fecal and urine samples and the whole-body counters‟ (WBC) data and are the main source of the quantitative data used for the dose assessment. The RPI radiochemical laboratories in Kyiv and at the Chornobyl site employed the standard radiochemical technique and equipped with ninety six alpha-spectrometers. The range of WBCs includes the scanning low-background WBC, four Canberra FastScan WBCs, and four chair-type WBCs. The car-borne WBC is located in Kiev and reserved for the emergency purposes. As on September 2017 the Internal Dosimetry Program has covered more than 17 000 workers, which undergone 1 230 000 measurements of ¹³⁷Cs on WBCs, 87 000 measurements of ²³⁹⁺²⁴⁰Pu contents in fecal samples and 4 400 measurements of ²³⁹⁺²⁴⁰Pu contents in urine samples. Such a large-scale programme ensured a reliable monitoring of intakes of the insoluble radioactive material.